Identification and quantification of a novel nitrate-reducing community in sediments of Suquía River basin along a nitrate gradient - Reyna, Luciana (2010)
We evaluated the molecular diversity of narG gene from Suquía River sediments to assess the impact of the nitrate concentration and water quality on the composition and structure of the nitrate-reducing bacterial community. To this aim, a library of one of the six monitoring stations corresponding to the highest nitrate concentration was constructed and 118 narG clones were screened. Nucleotide sequences were associated to narG gene from alpha-, beta-, delta-, gammaproteobacteria and Thermus thermophilus. Remarkably, 18% of clones contained narG genes with less than 69% similarity to narG sequences available in databases. Thus, indicating the presence of nitrate-reducing bacteria with novel narG genes, which were quantified by real-time PCR. Results show a variable number of narG copies, ranging from less than 1.0 × 102 to 5.0 × 104 copies per ng of DNA, which were associated with a decreased water quality index monitored along the basin at different times.